Optimization of distributed control discrete systems under the quadratic quality criterion - Janušauskaitė, Nijolė (Lietuvos matematikos rinkinys, 1999)
The quadratic functional minimization problem was analysed. The motion trajectory was assumed to be discrete, the optimal control feedback was obtained.